KETIDAKSADARAN KOLEKTIF TOKOH DALAM NOVEL ANAK RANTAU KARYA AHMAD FUADI: KAJIAN PSIOKOLOGI ANALITIS CARLGUSTAV JUNG - Riskal Ahmad (TELAGA BAHASA, 2020)
Literary works are closely related to everyday human life and are the thoughts or expressions of the author. Literary works as the author's expression represent experiences, thoughts, feelings, and ideas expressed by using language as the medium. This study aims to analyze the collective unconsciousness of the characters in Ahmad Fuadi's novel Anak Rantau through the psychoanalytic approach of Carl Gustav Jung. This research is a type of library research. The research data is in the form of a novel entitled Anak Rantau by Ahmad Fuadi. The method used in this research is a descriptive qualitative method. From the results of the study, it was found: (1) the personal role of Datuk Marajo, which displays a different character to cover the character that belongs to him, (2) the role of the archetype of anima in Martiaz, namely the feminine side of a man, (3) ) the role of shadow (shadow) in the character Jenggo to cover his mistakes, and (4) the role of self-archetype (self) in Datuk Marajo to get calm.